A Review on Impact of Deceptive Advertisement on Consumer Behaviour - Shukla, P; Karmakar, B (International Journal of Computer Sciences and Engineering, 2025)
An influential tool nowadays for any organization is Advertisement, as it not only helps in communicating the information to the customers about new product launched in the market but also induces them to purchase them. Companies usually follow unethical means to advertise their products, the term used for it is Misleading Advertisements. Misleading or false Advertisements is the use of wrong statements in advertisements for influencing customers to purchase the products, but it may negatively impact many customers. Many governments around the world use regulations and frame policies to control false and misleading advertisements, as advertisements have the potential to induce customers to buy products. The concept of the advertisements was that all the necessary information related to the product should be provided to customers using a global media that is the advertisement. This study is conducted to comprehend the impact of advertisements on customers using Medias and what can be done to improve the effectiveness